Выражение 1) 3z/2z+5y + 3x+6y/2z+5y 2)6x-3z/8x-4z + 8x+5z/8x-4z 3) 3c/2c + 7c-2k/2c 4) 6m+2d/8m-6d - 2m-3d/8m-6d 5) 5c-6b/c+6b + 6c-2b/c+6b

chuko chuko    1   07.09.2019 20:10    0

Ответы
DarKerThanBlaCK34 DarKerThanBlaCK34  16.08.2020 11:24
1) 3z/(2z+5y) + (3x+6y)/(2z+5y) = (3z+3x+6y)/(2z+5y) 
2) (6x-3z)/(8x-4z) + (8x+5z)/(8x-4z) = (6x-3z+8x+5z)/(8x-4z) = (14x+2z)/(8x-4z) = (2(7x+z))/(2(4x-2z)) = (7x+z)/(4x-2z) 
3) 3c/2c + (7c-2k)/2c = (3c+7c-2k)/2c = (10c-2k)/2c = (2(5c-k))/2c = (5c-k)/c 
ПОКАЗАТЬ ОТВЕТЫ
nastya84398 nastya84398  16.08.2020 11:24
Вот два примераи ответы нанего
Выражение 1) 3z/2z+5y + 3x+6y/2z+5y 2)6x-3z/8x-4z + 8x+5z/8x-4z 3) 3c/2c + 7c-2k/2c 4) 6m+2d/8m-6d -
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра